Assessment of Bank Erosion, Accretion and Channel Shifting Using Remote Sensing and GIS: Case Study – Lower Course of the Bosna River - Lovric, Novica; Tosic, Radislav (Quaestiones Geographicae, 2016)
River bank erosion, accretion and lateral channel migration are the most important geomorphological processes, which attract a great deal of attention from river engineering scientist over the last century. in the presented study, we assessed how the river’s shape and position have changed during 1958-2013 period using remote sensing and GIS. We have identified that the total area of bank erosion during given period equalled 8.3430 km2, of which 3.2593 km2 were on the left bank and 5.0837 km2 on the right bank. The total area of bank accretion from 1958 to 2013 equalled 10.7074 km2, of which 5.4115 km2 was on the left bank and 5.2958 km2 on the right bank. The Bosna riverbed average movement in the period 1958-2013 was established in the amount of 132.4 m. During this period, the average lateral channel migration was 2.5 m per year. The data presented here are significant for practical issues such as predicting channel migration rates for engineering and planning purposes, soil and water management.